Elevated iron stores are associated with HIV disease severity and mortality among postpartum women in Zimbabwe - Rawat, Rahul; Humphrey, J. H.; Ntozini, R.; Mutasa, K.; Iliff, P. J.; Stoltzfus, Rebecca J. (Cambridge University Press, 2009)
The relationship between Fe status and HIV infection is complex and poorly understood. While anaemia is a major complication of HIV infection, higher Fe stores may be associated with disease progression. There is limited and conflicting data available from Africa.Cross-sectional and prospective cohort study.We examined the association between postpartum Fe status (Hb, serum ferritin (SF) and transferrin receptor (TfR)) and viral load (VL) and HIV-related mortality in 643 HIV-positive Zimbabwean women over a period of 12 months.In non-anaemic women a log10increase in SF was associated with a 2·3-fold increase in VL (P= 0·019); this association was absent in anaemic women. In prospective analyses, a log10increase in SF was associated with a 4-fold increase in mortality by 12 months (P= 0·002). Hb was negatively associated with VL (P= 0·001) and mortality (P= 0·047). The adverse associations between SF and both VL and mortality were found at SF concentrations >45 μg/l (P< 0·05). Controlling for α1acid glycoprotein, a marker of inflammation, attenuated the association between both SF and VL and mortality, but these remained significant.These results are consistent with the hypothesis that high Fe stores have adverse consequences in HIV infection. If adverse consequences are real, our data suggest that they occur at SF concentrations exceeding those consistent with adequate Fe nutriture.